Inequality, joint participation and (re) distributive challenges in the Argentina Republic - Rezzoagli, Luciano Carlos (2015)
The fiscal correspondence and a giving - back vision of fiscal and financial relationships between different scalar spheres is valid and adequate when the competence features are similar between subnational entities. But, in a clear situation of regional asymmetry (many Argentinas within the same Argentina), in a country that belongs to the most unequal continent in the World, this vision threatens the possibility of citizens living peripheral areas to enforce their constitutional rights and enable their development.The constitutional reform from 1994 incorporated among its multiple changes and additions, a substantial innovation in terms of fiscal federalism: the privileged hierarchization of the federal revenue sharing regime. In this way, the constitutional principles and purposes that may develop from the financial and tax field were consolidated. The principles of regional harmonious prosperity and equal human development acquired special emphasis in the spirit of the preexisting joint participation regime. Moreover, in the sixth transitional clause they established an express mandate to reelaborate the then current regime. The distance between the constitution and the fiscal reality becomes insurmountable until there exists a clarifying position regarding the ambiguity of the dominant discourses about fiscal decentralization that tend to consolidate the weakness of the state institutions in the country, and the growth of the regional asymmetries with their respective populational migration flow towards the cities with greater resources and/or their peripheries.